The Effect of Variations in Current and Time to Manufacture Powder Tin (Sn) via Electrodeposition Process - Raden Henny Mulyani; Yuliani Carisca Tanjung; Djoko Hadi Prajitno (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2019)
Manufacture of powder metallurgy through the process of electrolysis, resulting in the phenomenon of deposition on the cathode. Electrolysis process produces high purity but many compounds decompose participating will affect its purity. Pulverizing tin (Sn) is done by varying the amount of current (5 A , 6 A and 7 A) and processing time (20 minutes , 25 minutes and 30 minutes) with variable fixed temperature of 50 ° C and solution concentration of 0.01 M. Electrode used is stainless steel 304 as the cathode and tin (Sn) as the anode. Powder tin (Sn) generated reaches 80 % , the most current efficiency is obtained from the current 6 A with a time of 20 minutes and the lowest energy consumption derived from the current of 5 A at 20 , 25 and 30 minutes at 4.6 KWH / kg Sn. From the results obtained are expected to be a material consideration in producing powder tin (Sn).